2014
DOI: 10.1117/12.2085138
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of contamination growth and damage by absorption centers under UV irradiation

Abstract: Contamination plays a major role in lifetime of vacuum optics. Several efforts have been made to derive suitable models for lifetime prediction in laser-induced contamination related optical breakdown. But the broad spectrum of potential contaminants present in the various applications with their very specific contamination mechanisms complicates the derivation of universal optics degradation models.As one possible contamination initiation process, the impact of optical absorption on the laser-induced contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…[18][19][20][21][22] This effect is critical for the industrial applications, and it has mainly been studied in the context of space applications: several past spaceflight missions using ns UV lasers proved to be short-lived and unreliable due to this effect, which has initiated an active field of research between space and laser communities. [23][24][25][26][27][28][29][30] LIC effects in the fs/ps regime have not been reported in the opened literature up to now but our investigations on laser components have led us to the 3 conclusion that these effects are also particularly detrimental in this regime and can be a main limitation of short wavelength high average power fs/ps lasers (Figure 1). Therefore, in this work we would like to investigate these effects with a first report on the topic.…”
Section: Introductionmentioning
confidence: 87%
“…[18][19][20][21][22] This effect is critical for the industrial applications, and it has mainly been studied in the context of space applications: several past spaceflight missions using ns UV lasers proved to be short-lived and unreliable due to this effect, which has initiated an active field of research between space and laser communities. [23][24][25][26][27][28][29][30] LIC effects in the fs/ps regime have not been reported in the opened literature up to now but our investigations on laser components have led us to the 3 conclusion that these effects are also particularly detrimental in this regime and can be a main limitation of short wavelength high average power fs/ps lasers (Figure 1). Therefore, in this work we would like to investigate these effects with a first report on the topic.…”
Section: Introductionmentioning
confidence: 87%
“…In fact, we have recently shown that the localized heating of nano-inclusions can enhance LIMC via local heating, even though the nanometersized inclusions are not in direct contact with the contaminant. 28,29 Thus, in future work we would like to assess, whether laser conditioning (either after or during the coating process) also benefits the mitigation of laser-induced damage for high-power laser optics in "real world", space-like environments.…”
Section: Discussionmentioning
confidence: 99%
“…There are various experimental setups available in the scientific community for conducting LIC tests. Some of the setups 20,22,[25][26][27][28][29] were used to test optics intended for space applications, with an emphasis on study in the nanosecond UV regime. In this case, a high vacuum chamber is utilized to simulate space conditions, and the contamination growth is regulated by inserting a selected contaminant into the chamber.…”
Section: Experiments Descriptionmentioning
confidence: 99%